The utility of serology for elimination surveillance of trachoma. Issue 1 (December 2018) - Pinsent, Amy; Solomon, Anthony; Bailey, Robin; Bid, Rhiannon; Cama, Anaseini; Dean, Deborah; Goodhew, Brook; Gwyn, Sarah; Jack, Kelvin; Kandel, Ram; Kama, Mike; Massae, Patrick; et al.
Abstract Robust surveillance methods are needed for trachoma control and recrudescence monitoring, but existing methods have limitations. Here, we analyse data from nine trachoma-endemic populations and provide operational thresholds for interpretation of serological data in low-transmission and post-elimination settings. Analyses with sero-catalytic and antibody acquisition models provide insights into transmission history within each population. To accurately estimate sero-conversion rates (SCR) for trachoma in populations with high-seroprevalence in adults, the model accounts for secondary exposure toChlamydia trachomatis due to urogenital infection. We estimate the population half-life of sero-reversion for anti-Pgp3 antibodies to be 26 (95% credible interval (CrI): 21–34) years. We show SCRs below 0.015 (95% confidence interval (CI): 0.0–0.049) per year correspond to a prevalence of trachomatous inflammation—follicular below 5%, the current threshold for elimination of active trachoma as a public health problem. As global trachoma prevalence declines, we may need cross-sectional serological survey data to inform programmatic decisions. Robust surveillance methods are needed for trachoma control and recrudescence monitoring, but existing methods have limitations. Here, Pinsent et al. analyse data from nine trachoma-endemic populations and provide operational thresholds for interpretation of serological data in low transmission and post-elimination settings.